2013
DOI: 10.1111/1744-9987.12003
|View full text |Cite
|
Sign up to set email alerts
|

Distal Radial Artery Pressures Predict Angiographic Result and Short‐Term Patency Outcome in Hemodialysis Patients With Juxta‐Anastomotic Inflow Stenosis of Radiocephalic Fistula Undergoing Transradial Angioplasty

Abstract: Distal radial artery pressure (RAP) was observed to be reduced after transradial percutaneous transluminal angioplasty (PTA) on the juxta-anastomotic venous stenosis of radiocephalic arteriovenous fistula (RCAVF). Distal RAPs are easily obtained from a pressure transducer connected with an introducer retrograde inserted into distal radial artery. The clinical role of distal RAP in the setting of transradial PTA remains unknown. This prospective and observational study aimed to explore the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The study also had nearly 60% procedure failure and residual stenosis of >60% reinforcing angiography’s weakness as a marker of efficiency. Lai et al 11 also reported distal radial artery pressure measured at the time of procedure as a marker of angiographic outcomes and 3-month primary access patency. Reported studies to date are limited to intraprocedural measurements that require additional resources, adds to procedure times, cost, and specific access types.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also had nearly 60% procedure failure and residual stenosis of >60% reinforcing angiography’s weakness as a marker of efficiency. Lai et al 11 also reported distal radial artery pressure measured at the time of procedure as a marker of angiographic outcomes and 3-month primary access patency. Reported studies to date are limited to intraprocedural measurements that require additional resources, adds to procedure times, cost, and specific access types.…”
Section: Discussionmentioning
confidence: 99%
“…10 Distal radial artery pressure gradient, translesional pressure ratio, and catheter-based flow studies are proposed to predict technical and patency outcomes in limited VA types and require additional resources. [11][12][13][14] These adjunctive methods are useful intraprocedure but have limited applicability across various access types and clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…Although the National Kidney Foundation-Kidney Disease Outcomes Quality Initiative clinical practice guideline has recommended angiographic and hemodynamic criteria for determining technical success in percutaneous transluminal angioplasty (PTA) on dysfunctional arteriovenous access (1), inconsistent angiographic and functional results are commonly encountered (24). Several hemodynamic parameters have been applied to help evaluate the lesions in addition to visually angiographic assessments, such as an intra-access pressure (57), distal radial artery pressure (8), a pressure ratio of the intra-access pressure over systemic artery pressure (911) and an access blood flow (3, 12, 13). A translesional pressure ratio (TLPR) representing fractional flow reserve (FFR) has been increasingly utilized for hemodynamic and functional assessments of the moderate coronary stenosis in percutaneous coronary intervention (PCI) with an attempt to overcome angiographic limitations (1421).…”
Section: Introductionmentioning
confidence: 99%